Effects of Childhood Maltreatment on Self-Compassion: A Systematic Review and Meta-Analysis. (April 2023) - Zhang, Huiping; Li, Jiming; Sun, Bingyi; Wei, Qingong
Background: This systematic review aims to estimate the extent to which childhood maltreatment influences self-compassion in later life. Method: Four English databases (Web of Science, PsycINFO, PubMed, and PsycARTICLES) and three Chinese databases (China National Knowledge Infrastructure, Wanfang, and Weipu) were systematically searched. We extracted data related to the associations between child maltreatment and self-compassion and pooled them using random effect models. Findings: A total of 20 eligible studies were included involving 6, 877 participants in the analyses. Overall child maltreatment was negatively related to self-compassion ( r = −.28, p < .001); emotional abuse and neglect were negatively related to self-compassion ( r = −.28, p < .01; r = −.31, p < .01, respectively) at a moderate level; and physical abuse, sexual abuse, and physical neglect were negatively related to self-compassion ( r = −.12, p < .01; r = −.10, p < .01; and r = −.22, p < .001, respectively) at a small level. Conclusion: The results indicate that overall and subtypes of maltreatment are associated with decreased self-compassion, and child intervention programs focused on self-compassion should be designed to protect the well-being of individuals with a history of childhood maltreatment.